PERAN PEREMPUAN DALAM MELESTARIKAN LINGKUNGAN - Rosita Carolina (Universitas Negeri Medan, 2013)
ABSTRACT Women should have the instinct to perform life activities in order to meet the needs of daily life for his family. The necessities of life varies depending on each family income level and ability. Environmental degradation such as deforestation or land use change with another function that will change the composition of habitat for living organisms. Environmental programs are so heavily propagandized by the government should involve women. Women who are regarded weak should also proactive in influencing decision making oriented environment. Kata Kunci : Perempuan, lingkungan.